EDUKASI GIZI MENU SNACK SEHAT BERBASIS PANGAN LOKAL PADA SISWA SMPN 2 BAYANG DI KABUPATEN PESISIR SELATAN - Putri Aulia Arza; Yeffi Masnarivan; Ike Luthfiana Dewi; Salsabilla Nurul Afifah (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Consumption of healthy snacks in children is very important to note, this is because it will have an impact on the health and nutritional status of the child. The nutritional status of children will affect the quality of human resources from school to productive age. The purpose of this activity is to increase the knowledge of junior high school students about healthy snack menus based on local food. The method of this activity is to conduct nutrition education and evaluate the increase in student's knowledge by using a questionnaire. This activity begins with an introduction and continues with a pre-test. Furthermore, nutrition education in the form of providing interesting materials and videos in choosing healthy snacks based on local food, post-test, discussion, and question and answer. To increase the enthusiasm of the participants, prizes were given. The results of the activities obtained by nutrition education at SMPN 2 Bayang can increase the knowledge of junior high school children about how to choose healthy snacks based on local food. This can be seen from the difference in the level of students' knowledge before (pre-test) and after (post-test) regarding the nutrition education provided. Besides, when students are served some snacks, students can choose and explain healthy and unhealthy foods. Some of the various local snacks and processed forms such as sweet potatoes, corn, taro can also be described in detail by students. From the activities that have been carried out, it can be concluded that nutrition education increases student’s knowledge about how to choose healthy snacks based on local food.